Explicit finite element modelling of heel pad mechanics in running: inclusion of body dynamics and application of physiological impact loads - Chen, W.-M.; Lee, P. V.-S. (Computer Methods in Biomechanics and Biomedical Engineering, 2015)
Many heel pathologies including plantar heel pain may result from micro tears/trauma in the subcutaneous tissues, in which internal tissue deformation/stresses within the heel pad play an important role. Previously, many finite element models have been proposed to evaluate stresses inside the heel pad, but the majority of these models only focus on static loading boundary conditions. This study explored a dynamics modelling approach to the heel pad subjected to realistic impact loads during running. In this model, the inertial property and action of the body are described by a lumped parameter model, while the heel/shoe interactions are modelled using a viscoelastic heel pad model with contact properties. The impact force pattern, dynamic heel pad deformation and stress states predicted by the model were compared with published experimental data. Further parametrical studies revealed the model responses, in terms of internal stresses in the skin and fatty tissue, change nonlinearly when body dynamics changes. A reduction in foot's touchdown velocity resulted in a less severe impact landing and stress relief inside the heel pad, for example peak von-Mises stress in fatty tissue, was reduced by 11.3%. Applications of the model may be extendable to perform iterative analyses to further understand the complex relationships between body dynamics and stress distributions in the soft tissue of heel pad during running. This may open new opportunities to study the mechanical aetiology of plantar heel pain in runners.